Outcome Measures in Adult Spine Surgery: How Do We Identify the Outcomes of Greatest Utility for Research?. Issue 4 (May 2019) - Slattery, Casey; Verma, Kushagra
Abstract : The goal of any surgical intervention in spine surgery is to restore function, relieve pain, and improve quality of life. Traditional assessments of patient outcomes failed to accurately reflect patient's quality of life improvement. Patient-reported outcome measures (PROM) were designed to translate the patients perceived health into quantitative data. The data can help providers gauge the severity of a condition, develop a treatment plan, and follow the patient over time to determine treatment efficacy. Both in clinical practice and research, PROMs are helpful in comparing treatment options and advancing the field of spine surgery. This article discusses the utility and reliability of patient-reported outcomes, utilization in research, and provides examples of the most widely utilized PROMs in spine surgery.